(untitled) (Research, Society and Development, 2024)
This study presents reflections on school teaching and teaching in the current social context strongly influenced by the development and diffusion of digital technologies in society. It aims to discuss some of the implications that the presence of elements of digital culture has presented to the context of school teaching and teaching today. Through an exploratory study and based on the ideas of scholars such as Pierre Lévy, Manuel Castells, Paulo Freire, among others, the aim is to hold a discussion aimed at broadening educational perspectives that seek to understand more about school teaching and teaching in the present. The considerations presented in this text allow us to affirm that reflections that seek to direct the realization of a school performance committed to the formation of ethical, responsible people capable of exercising citizenship need to be a permanent practice, especially for those involved in the school education process in an increasingly interconnected, challenging and uncertain scenario.